Out-of-pocket costs associated with rotavirus gastroenteritis requiring hospitalization in Malaysia - Chai, P.F.; Lee, W.S. (2009)
From August 2006 to July 2007 a prospective study of out-of-pocket costs incurred by care-givers of children hospitalized for rotavirus gastroenteritis was conducted in a hospital in Malaysia. Data on caretaker out-of-pocket costs were collected from 260 children hospitalized with diarrhoea. A stool sample was collected from 198 of these children of which 46 (23) were positive for rotavirus by latex agglutination assay. The mean (median; interquartile range) out-of-pocket cost incurred by the care-givers was US194 (US169: US47-738), constituting 26 of average monthly income of the households surveyed. Major components of the cost were hospital expenses (45) and productivity loss (37). These findings will allow further assessment of the cost-effectiveness of any future rotavirus immunization program in Malaysia. (C) 2009 Elsevier Ltd. All rights reserved.